Analisis Faktor yang Mempengaruhi Struktur Modal pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017 - Mariska Leviani dan Indra Widjaja (Universitas Tarumanagara, 2020)
This research aimed to examine the effect of Liquidity (Current Ratio), Profitability (Return On Assets), Sales Growth, and Firm Size toward Capital Structure (Debt to Equity Ratio) on manufacturing companies sector food and beverages in Indonesia Stock Exchange for period 2013 - 2017. The sampling technique used was purposive sampling and the sample collected consisted of 14 companies. Analysis using SPSS program. Based on statistical t test, the result of research show that Liquidity had a significant, negative effect on Capital Structure. Meanwhile, Profitability, Sales Growth, and Firm Size did not affect Capital Structure. Based on statistical F test indicates that variables Liquidity, Profitability, Sales Growth, and Firm Size simultantly affect Capital Structure on manufacturing companies sector food and beverage listed in Indonesia Stock Exchange for period 2013 - 2017.